2014
DOI: 10.1590/s0100-83582014000400003
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de plantas daninhas eudicotiledôneas na cultura da soja Roundup Ready

Abstract: RESUMO -As espécies eudicotiledôneas sempre foram um desafio no manejo de plantas daninhas na cultura da soja. Essa dificuldade foi aumentada pelo surgimento de plantas de difícil controle com os herbicidas atualmente existentes no mercado. Diante disso, o objetivo deste trabalho foi o de buscar alternativas de manejo que diminuam a pressão de seleção devido ao uso contínuo de glifosato na soja Roundup Ready ® . O trabalho foi implantado no delineamento em blocos casualizados, em esquema de parcelas sub-subdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Arrow-leaf sida is considered strongly competitive with agricultural crops because it has a very deep root system and survives in inhospitable environments (Constantin et al, 2007), in addition to hindering mechanical harvesting in annual crops due to stem resistance. Due to the damages arrow-leaf sida causes to soybean, management practices are necessary by combining control actions in addition to identifying soybean cultivars that present better competitive ability in the presence of weeds (Rizzardi & Silva, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Arrow-leaf sida is considered strongly competitive with agricultural crops because it has a very deep root system and survives in inhospitable environments (Constantin et al, 2007), in addition to hindering mechanical harvesting in annual crops due to stem resistance. Due to the damages arrow-leaf sida causes to soybean, management practices are necessary by combining control actions in addition to identifying soybean cultivars that present better competitive ability in the presence of weeds (Rizzardi & Silva, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to ALS-inhibiting herbicides was found for chemical groups of imidazolinones, sulfonylureas and triazolopyrimidines (PRIGOL et al, 2014), as observed by this study. Unsatisfactory control of biotypes 20.2 and 21.1 by ALS-inhibiting herbicides, associated with low resistance to the herbicide glyphosate, may even hinder its management in soybean crops since their mutual and abusive use may submit wild poinsettia plants to high selection pressure (TREZZI et al, 2011;COSTA;RIZZARDI, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Wild poinsettia (Euphorbia heterophylla L.) is a weed Euphorbiaceae which has been known as one of the most important infestant of soybean crops (TREZZI et al, 2006;SILVA, 2014). The species causes economic loss, since it features high ability to compete for resources in the environment and may decrease productivity, affect the quality of the product and hinder harvesting operations (CARVALHO et al, 2010, VARGAS et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…P. ruderale and T. procumbens weeds were more numerous in the fallow area than in the treatments with cover crops (Table 3), which indicates that there is a greater proliferation of these species when there is no control by the cover crops phytomass. Rizzardi and Silva (2014) studied management strategies to prevent the emergence of weeds in soybean crop, and Martins et al (2016) in maize crop, reported that in fallow areas, managed with or without chemical control, contribute to the proliferation and a more difficult control of weeds. T. procumbens was found in fallow areas at all times, and in the evaluation at the time of desiccation for planting soybean, it was found in the area with P. glaucum.…”
Section: Resultsmentioning
confidence: 99%